Translation Method and Meaning Equivalence in The Song Lyric “Let It Go Sung” By Idina Menzel and “Biarkan” By Nadya Almira Puteri - Selfi Aulia Ramadhani; Otong Setiawan Djuharie (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze the translation method and meaning equivalence in the song lyrics "Let It Go" sung by Idina Menzel and its translated version "Biarkan" by Nadya Almira Puteri. Using a qualitative approach, this research explores how linguistic and cultural elements in the original lyrics are translated into Indonesian. The translation methods examined in this analysis include literal translation, free translation, and adaptation, as well as how each method affects the meaning equivalence between the two versions. The findings indicate that although there are differences in structure and word choice, the translation "Biarkan" successfully retains the core message and emotions contained in the lyrics of "Let It Go." This study is expected to provide deeper insights into the challenges and strategies involved in translating song lyrics, as well as its contributions to cross-cultural understanding.